Information politics, transnational advocacy and education for all - Magrath, Bronwen (University of Chicago Press, 2015)
Introduction: Successful advocacy requires research. Advocacy organizations need to gather evidence to show the extent of a particular social problem, the lack of official response to the problem, and solutions that could be fostered from the ground up. The process of gathering information and using it for political advocacy has been termed “information politics” (Keck & Sikkink 1998). In the past two decades, civil society organizations have played an increasingly prominent role in global educational advocacy and governance (Mundy & Murphy 2001; Mundy 2007). Civil society organizations carry out a significant amount of research into the (lack of) progress made on Education for All goals, monitoring and evaluating education policy and practice at local, national and regional levels, and offering alternative approaches to meet EFA targets. Yet little has been done to examine the evidence-gathering process to see what it can tell us about the role of advocacy research in education policy and the wider role of civil society in global educational change. This paper seeks to contribute to our understanding of evidence-based advocacy and educational governance. In order to do so, I examine information politics as carried out by two civil society organizations in the Education for All (EFA) movement. One is ActionAid International, a large international development NGO originally based in the UK but now headquartered in Johannesburg. The other is the Asian South Pacific Association for Basic and Adult Education (ASPBAE), a regional network of education practitioners and activists currently headquartered in Mumbai. I explore one example of information politics carried out by each of my case study organizations: ActionAid’s International Benchmarks on Adult Literacy, and ASPBAE’s Asia South-Pacific Education Watch. My intention here is to shed light on how information is collected and disseminated by advocacy NGOs, and what this tells us about the internal dynamics and strategies of these organizations as well as the wider development education field of which they are a part.